FACTORS AFFECTING THE INCOME OF FRESH SEA FISH TRADERS IN THE FLAMBOYAN MARKET OF TANJUNG SAWIT VILLAGE, TAPUNG SUB-DISTRICT, KAMPAR REGENCY - Daniel Pangihutan; Trisla Warningsih; Darwis AN (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research aimed to know and to calculate the income of fresh seafood retailers in the Flamboyan Market, to analize the effects (capital, bussiness experience and education level. This research was conducted in December 2019. The method used within this research was survey method. There were 12 respondents as ritailers used within this research. The result of the research showed that the income range of ritailers was IDR Rp 2.130,000,- until IDR 9.740,000,- and there are 3 ritailers who have income under Kampar Regency’s UMR in 2009, namely IDR 2.719,000 . From the three variables analyzed, it can be seen that capital (X1), business experience (X2) and education level (X3) have regression coefficients (bi), namely (0.568), (0.706) and (0.129). The standard error of the independent variables ( Sbi) for that capital (X1), business experience (X2) and education level (X3) are (0.245), (0.292) and (0.262). This shows that the relationship between capital (X1), business experience (X2) and education level (X3) on the income of fresh marine fish retailers (Y) is unidirectional (positive). This means that with the increase in capital, Business Experience and Education Level will increase the income of fresh marine fish retailers.